HYGENICITY AND NUTRITIONAL QUALITY OF TRADITIONAL DRIED AND SMOKED FISHES AT KAWARDHA FISH MARKET, (CHHATTISGARH), INDIA - JITENDER KUMAR JAKHAR,; ANIRUDH KUMAR,; H. K. VARDIA, (The Bioscan, 2015)
Microbial load was determined as (log10 Cfu/g) fresh fish (Mystus tengara), fresh prawn (Macrobrachium lamarrei), dried and smoked fish (Mystus tengara) obtained from fish market in Kawardha town. Smoked fish had the lowest bacterial count (4.84ab±0.15) while dried fish had highest bacteria count (8.50c±0.76). The fresh fish and fresh prawn had the medium bacterial count of 6.33b±0.08 and 5.42a±0.07 respectively. The moisture content for fresh fish and fresh prawn were 72.34±1.45% and 63.00±1.53% respectively. The moisture content was reduced to 14.34a±2.34 % and 22.67b±1.45 % for smoked and sun dried fish respectively. The protein content in smoked dried fish was the highest (40.00d±1.15 %) in comparison to fresh prawn (17.50b±0.87%), fresh fish (13.34a±0.60%) and dried fish (23.34c±1.45%) respectively. Total ash content obtained in this study were 1.74a±0.15%, 2.50a±0.29%, 3.50b±0.40% and 5.07c±0.35% for fresh prawn, fresh fish, dried fish and smoked fish respectively. Higher total plate count of 106/g or above is considered to be of poor quality for fish. In the present study it was found that total plate count for fresh fish, prawn and smoked fish was under the acceptable limit (106/g) except for smoked fish.